The Environmental Kuznets Curve and Globalization: The Empirical Evidence for Portugal, Spain, Greece and Ireland - Leitão, Nuno Carlos (Energy Economics Letters, 2013)
The main objective of this manuscript is to investagte the relationship between environmental Kuznets curve (ECK) in the presence of globalization for Portugal, Spain, Greece and Ireland for the period of 1980-2010. Using a panel data, the results show that linear and non-linear real income per capita ( and ) are according to the perspectives of inverted-U shaped between economic growth and CO2 emissions. The findings support the theory that in general, there is a positive correlation between of energy consumption with CO2 emissions.